Pronósticos de los créditos directos y depósitos a plazo de las Cajas Municipales de Loreto periodo 2018 – 2022 - Salas Guevara, Mario Christian (2025)
This thesis analyzed the behavior of credits and deposits in the Municipal Savings Banks of Loreto during the period 2018-2022, using ARIMA models for forecasting. Credits showed a general upward trend, with fluctuations and a notable impact due to the COVID-19 pandemic. A significant drop was observed in March 2020, followed by a rapid recovery from July of the same year. The average value of credits during the period was S/ 343,486.90 thousand. Deposits also exhibited a fluctuating pattern with an upward trend, interrupted by the health crisis. After the initial fall, a rapid recovery was observed from May 2020. The average value of deposits was S/ 245,748.51 thousand. The average ratio of credits to deposits was 1.4, indicating that Loreto's microfinance market is credit-demanding. Regarding forecasts, an ARIMA (1,1,1) model was selected for credits and an ARIMA (0,1,1) for deposits. These models demonstrated high precision, with error margins of 0.43% for credits and 0.8% for deposits, both well below the established 5% threshold. The results suggest partially sustained growth in the sector, with credits showing a positive trend (average monthly growth of 0.2%) and deposits presenting stability (zero growth). These findings provide valuable insights into the dynamics of the microfinance sector in Loreto and offer precise predictive tools to anticipate future trends in credits and deposits.